Polymerization of ɛ-caprolactone using ruthenium(II) mixed metallocene catalysts and isopropyl alcohol: Living character and mechanistic study - Mendes, Paulo J.G. (2012)
A series of ruthenium(II) complexes with the general formula [Ru(η5-C5H5) (η6-substituted arene)]+[PF6]− (substituted arene = 2-phenylpyridine (1), dibenzosuberone (2) and toluene (3)), in combination with isopropyl alcohol were used for the polymerization of ɛ-caprolactone. The polymerization was found to be quantitative and controlled, with PDI in the range 1.1–1.3. By means of MALDI-ToF analyses, functionalization studies with d,l-lactide and NMR monitoring techniques, it has been found that the polymerization proceeds via a living Activated Monomer mechanism (AM) involving an η6–η4 change of the coordination mode of the arene. These experimental results were corroborated by DFT studies. The growth of several polymer chains per ruthenium atom highlights interesting potentialities for molecular weight control and catalyst economy. The stability of the ruthenium complexes allows their recovery at the end of the polymerization, which can be viewed as a further advance in a green chemistry frame.